2006
DOI: 10.1126/science.1121479
|View full text |Cite
|
Sign up to set email alerts
|

Mission Creep in the IRB World

Abstract: THE SYSTEM IN THE UNITED STATES FOR PROTECTING HUMAN PARTICIPANTS IN RESEARCHengages the earnest efforts of thousands of scientists, community volunteers, and administrators. Through untold hours of service on Institutional Review Boards (IRBs), they watch over the safety of human research subjects. Unfortunately, much of that effort is increasingly misdirected as the system succumbs to "mission creep" that could compromise its central goals. Our IRB system is endangered by excessive paperwork and expanding ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 0 publications
0
69
0
Order By: Relevance
“…This may be due to the presence of unforeseen risks as well as the tendencies of investigators to overplay the benefits of experimental treatments, where accurate outcomes are uncertain. Others have suggested that the legalistic culture of expanding obligations of IRBs to oversee clinical research results in overregulation and underproduction, which compromises the central goals of clinical research [21].…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the presence of unforeseen risks as well as the tendencies of investigators to overplay the benefits of experimental treatments, where accurate outcomes are uncertain. Others have suggested that the legalistic culture of expanding obligations of IRBs to oversee clinical research results in overregulation and underproduction, which compromises the central goals of clinical research [21].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors seem to question whether there is a future for the current MRECs in the assessments of medical research (Saunders 2002;Savulescu 2002). Others highlight the growing regulations and bureaucracy in medical research with human participants (Stewart et al 2008) and the mission creep of the reviewing committees (Gunsalus et al 2006).…”
Section: The Changing Landscape Of Medical Researchmentioning
confidence: 98%
“…In preventing sound and ethical research from being conducted or approving research that is ethically or methodologically unsound, IRBs can contribute to the diversion of participants, institutional resources, and limited funding away from important studies to trials that are unlikely to generate socially valuable knowledge. This threat has led some researchers to accuse IRBs of stifling progress and creativity (Hamburger 2007), discouraging good research (Gunsalus et al 2006), impeding biomedical progress (Epstein 2007), misdirecting scarce resources (Gunsalus et al 2006;Whitney et al 2008), and even possibly encouraging research misconduct (Keith-Spiegel and…”
Section: Barriers To Effective Deliberation In Clinical Research Overmentioning
confidence: 99%